Therapeutic Potential of Aceh's Syzygium polyanthum in Reducing Uric Acid in Rattus Norvegicus - Nasrullah, Nasrullah; Siregar, Masra Lena; Suryawati, Suryawati (Heca Sentra Analitika, 2024)
This research aims to evaluate the anti-hyperuricemic activity of Syzygium polyanthum ethanolic extract in hyperuricemic male rats (Rattus norvegicus) induced by liver juice. A total of 25 animals were divided into five groups: a negative control group, a positive control group, and three treatment groups receiving S. polyanthum extract at doses of 150, 200, and 250 mg/kg body weight, respectively. The result showed that the dose of 250 mg/kg body weight resulted in the highest decrease of uric acid plasma, measuring 3.44 ± 2.03 mg/dL. This reduction is comparable to the effect of allopurinol, which showed a decrease of 3.70 ± 1.54 mg/dL. A minimum dose-dependent activity was observed. To conclude, the administration of ethanolic extract of S. polyanthum for 14 days significantly reduced uric acid levels. Further exploration of higher doses or a long-term treatment period to enhance its effectiveness is needed.